Effect of Temperature on Radiation-use Efficiency in Toria (Brassica campestris var. Toria) Crop - Nehra, D S; Singh, Raj; Niwas, Ram; Bishnoi, O P (Annals of Arid Zone, 2016)
A field experiment was conducted on toria (Brassica campeslris Var. toria) crop for three seasons (1989-90 to 1992-93) to study the effect of temperature on radiation-use efriciency (RUE). Two cultuvars, ’Sangam’ and ’TH 68’, were sown on three dates. Delay in sowing from first week of September to first week of October significantly increased the RUE. Efficiencies varied from 3.07 to 4.07 g dry mailer MJ-1 of intercepted photosynthetically active radiation for tori a crop in three different years. Across years, varieties and sowing dates. RUE and mean temperature of the whole season were negatively associated (r = -0.75).